Perbandingan Madu Karet dan Madu Rambutan Berdasarkan Kadar Air, Aktivitas Enzim Diastase dan Hidroximetilfurfural (HMF) (Faculty of Animal Science Universitas Brawijaya, 2015)
The purpose of this research was to determine the water content, diastase enzyme activity and HMF of the rubber and rambutan honey. The method was a laboratory experiments with statistical analysis unpaired student t-test by two treatments and fifteen replications. The variable of this research were water content, diastase enzyme activity and HMF. The results of rubber and rambutan honey showed that there were significant difference effect (P<0.05) water content of 21.59 ±0.76 % and 19.94 ±0.23%, the average diastase enzyme activity of the same (P>0.05) that is 11 DN and there is a highly significant difference (P<0.01) on the HMF content of 17.23±0.54 mg/kg and 7.61±0.23 mg/kg. Rubber and rambutan honey have good quality based on the water content, diastase enzyme activity and HMF. It was concluded that the rubber and rambutan honey used were of good quality because it has met the requirements of SNI.